Sources, Outcomes, and Resolution of Conflicts in Marriage among Iranian women: A qualitative study - Zahra Sadat Asadi; Roya Sadeghi; Mohammad Hossein Taghdisi; Freshteh Zamani-Alavijeh; Davoud Shojaeizadeh; Ali Reza Khoshdel (Electronic Physician, 2016)
Introduction: Family’s conflict is the important determinant of the quality and quantity of relationships among family members. No study of which we are aware has assessed conflicts, especially among normal or apparently satisfied couples in the Iranian context. This study explored that how women deal with different points, ideas and behaviors in marital life. Methods: For the study, we recruited 30 to 45-year-old housewives who visited health centers in Tehran, Iran. The participants (n = 45) were selected using purposefully convenient sampling. In-depth interviews and focus group discussions were used. The data were analyzed qualitatively using MAXQDA 10. Results: Themes, including conflicting situations, causes of conflict, consequences of conflict, and conflict resolution styles were extracted.